Wide tunable bandpass filter design based on CMOS active inductor - Sunça, Abdullah. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
RF bandpass filters being commonly used in wireless communication systems are increasingly being implemented utilizing actively simulated inductors. Implementation of bandpass filters based on active inductors holds a number of alluring characteristics including a high passband center frequency, a large center frequency tuning range, a large and tunable quality factor subsequently a low insertion loss, and a low silicon consumption. The use of active inductors in RF bandpass filters, however, is faced to several tough challenges including poor noise performance, a limited dynamic range, and a high level of power consumption. For the telecommunication applications in the UHF band (300 MHz - 3 GHz), frequency tuning range of the active inductor based bandpass filter implementations in the literature is generally between 1-3 GHz without the usage of external capacitances. LC tank circuits are commonly formed with off-chip capacitances while circuit operation requires below 1 GHz. The desired capacitance value may not be available for achieving an operation in specific frequency and on-chip varactors are used for fine tuning of the inductance value. A large area is required for implementing an onchip varactor which needs to succeed a wide range capacitance tuning. If so, a control voltage is a must for determination of the capacitance value which is a potential burden for the bias requirements of the overall circuitry. The work done in this M.S. thesis is the design of a new wide tunable bandpass filter based on an introduced CMOS active inductor topology which consists of a back-to-back connected transistor pair together with one single transistor utilized for inductance tuning. This gyrator-C network achieves a wide tuning range with introducing an idea for the removal of the use of off-chip and on-chip capacitances by realizing inductance boosting and decaying technique for the selection of the desired frequency. Implemented in TSMC 0.18μm process, the wide tunable active inductor based bandpass filter offers a tuning range between 327 MHz and 2 GHz with a quality factor above 40.
Keywords: Electronic circuit design.; Low voltage integrated circuits -- Design and construction.; Radio circuits -- Design and construction.